2012
DOI: 10.1128/aem.01184-12
|View full text |Cite
|
Sign up to set email alerts
|

Transovarial Transmission of Rickettsia spp. and Organ-Specific Infection of the Whitefly Bemisia tabaci

Abstract: bThe whitefly Bemisia tabaci is a cosmopolitan insect pest that harbors Portiera aleyrodidarum, the primary obligatory symbiotic bacterium, and several facultative secondary symbionts. Secondary symbionts in B. tabaci are generally associated with the bacteriome, ensuring their vertical transmission; however, Rickettsia is an exception and occupies most of the body cavity, except the bacteriome. The mode of Rickettsia transfer between generations and its subcellular localization in insect organs have not been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
72
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 70 publications
6
72
0
1
Order By: Relevance
“…In contrast to the rest of the detected endosymbionts in this study, only Rickettsia showed a scattered localization pattern and was observed outside the bacteriome infecting tissues in the abdomen, thorax and head as was recently shown [57]. Rickettsia was shown to manipulate host reproduction in many arthropods [50], [52], and this fits well with its localization pattern in B. tabaci.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast to the rest of the detected endosymbionts in this study, only Rickettsia showed a scattered localization pattern and was observed outside the bacteriome infecting tissues in the abdomen, thorax and head as was recently shown [57]. Rickettsia was shown to manipulate host reproduction in many arthropods [50], [52], and this fits well with its localization pattern in B. tabaci.…”
Section: Discussionsupporting
confidence: 90%
“…Population of the B. tabaci B infected with the secondary symbionts Rickettsia and Hamiltonella , rearing conditions and establishment of iso-female strains of Rickettsia -free (R-) and Rickettsia -infected (R+) strains, were conducted as previously described (Brumin et al, 2012). Briefly, the populations were reared on cotton seedlings ( Gossypium hirsutum L. cv.…”
Section: Methodsmentioning
confidence: 99%
“…Two methods of DNA isolation were used to confirm the presence of Rickettsia or TYLCV: one for single insects and one for pools of insects. To isolate DNA from single insects for PCR, 20 adult B. tabaci were individually homogenized in lysis buffer as previously described (22,25). The lysate was then incubated at 65°C for 15 min, followed by incubation at 95°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Only Rickettsia localizes outside the bacteriocytes, appears in most of the body cavity, and infects the majority of the internal organs, excluding the bacteriocytes (22,23). Rickettsia infects B. tabaci's digestive, salivary, and reproductive organs and cells and reaches exceptionally high concentrations within the host (22). These recent findings raised the possibility that the unique localization patterns and infection of pivotal organs in the insect host may significantly influence the insect's biology.…”
mentioning
confidence: 99%
See 1 more Smart Citation